Unraveling Mycobacterium tuberculosis genomic diversity and evolution in Lisbon, Portugal, a highly drug resistant setting - Perdigão, João (2015)
BACKGROUND: Multidrug- (MDR) and extensively drug resistant (XDR) tuberculosis (TB) presents a challenge to disease control and elimination goals. In Lisbon, Portugal, specific and successful XDR-TB strains have been found in circulation for almost two decades. RESULTS: In the present study we have genotyped and sequenced the genomes of 56 Mycobacterium tuberculosis isolates recovered mostly from Lisbon. The genotyping data revealed three major clusters associated with MDR-TB, two of which are associated with XDR-TB. Whilst the genomic data contributed to elucidate the phylogenetic positioning of circulating MDR-TB strains, showing a high predominance of a single SNP cluster group 5. Furthermore, a genome-wide phylogeny analysis from these strains, together with 19 publicly available genomes of Mycobacterium tuberculosis clinical isolates, revealed two major clades responsible for M/XDR-TB in the region: Lisboa3 and Q1 (LAM).The data presented by this study yielded insights on microevolution and identification of novel compensatory mutations associated with rifampicin resistance in rpoB and rpoC. The screening for other structural variations revealed putative clade-defining variants. One deletion in PPE41, found among Lisboa3 isolates, is proposed to contribute to immune evasion and as a selective advantage. Insertion sequence (IS) mapping has also demonstrated the role of IS6110 as a major driver in mycobacterial evolution by affecting gene integrity and regulation. CONCLUSIONS: Globally, this study contributes with novel genome-wide phylogenetic data and has led to the identification of new genomic variants that support the notion of a growing genomic diversity facing both setting and host adaptation.